A novel performance metric for Virtual Network Embedding combining aspects of Blocking Probability and Embedding Cost - Dáalos, Enrique (2017)
Network Virtualization offers a solution for Future Internet and it is a key enabler for cloud computing applications. Virtual Network Embedding (VNE) problem deals with resource allocation of a physical infrastructure to Virtual Network Requests (VNRs). Several performance metrics are employed in order to evaluate the efficiency of specific VNE approaches. These existing metrics, mostly related to Infrastructure Provider profit, are computed at the end of the VNE process, after embedding many VNRs. This work proposes a novel performance metric, VNE-NP (VNE Normalized Profit) which combines aspects of the two metrics most used in the literature: Blocking Probability and Embedding Cost.